The role of state- business relations in the performance of Zambia’s food processing sub-sector - Hampwaye Godfrey; Jeppesen Soeren (Bulletin of Geography. Socio-Economic Series, 2014)
In ensuring growth and development collaborative State-Business relations (SBRs) matters, and with economic growth comes increasing levels of employment, options for poverty reduction and hence more equitable development. Whereas it is known that SBR matters at a macro-economic level, the concept of SBR has also been employed in a more or less all-encompassing way in the literature. Accordingly, while it is clear that SBRs work, there is lack knowledge about which dimensions of SBRs are the most important. Due to the continued importance of agriculture in many developing countries, processing of the food produced in the sector is a key manufacturing activity of high economic importance to many economies. Ensuring collaborative SBRs in the food processing industry is therefore of interest to growth and development, particularly as it is a sector about which little is known about the role of SBRs. The paper attempts to examine how and why SBRs matter to and influence the growth and performance of local owned firms in the food processing sub-sector in Zambia. In particular, the paper analyses the roles and influence of government regulations and policies compared to those of business associations for the performance of the food processing sector in Zambia. The paper draws on primary data from a survey of firms in the food processing sector which was conducted between 2013 and 2014. It is shown that while the majority of the Zambian food processing firms experienced growth over the last five years, with increased employment and in a number of cases growing earnings, this seems to have happened in spite of a business environment which is not particularly supportive. The firms’ experience is that the SBRs mainly constitute institutional barriers to the performance of firms and highlight that formal government institutions and polices are incapable of assisting the firms and in most cases government institutions formulate and enact insufficient support schemes.